Brain Based Learning Using Augmented Reality Technology as an Arabic Learning Media - Yolanda, Refiyana; Firdaus, Dadang; Hendri, Muspika; Zaharo, Zaharo (Jurusan Pendidikan Bahasa Arab IAIN Ponorogo, 2024)
In the rapidly evolving educational landscape, recent technological advances have ushered in a new era of possibilities for innovative learning methodologies. This research integrates Brain-Based Learning principles with Augmented Reality (AR) technology as Arabic language teaching media. This research includes qualitative research with the type of literature. Data sources come from literature related to Augmented Reality and Brain-Based Learning. The data analysis method uses the content analysis method. The results of the study show: 1) optimisation of brain performance through the integration of Augmented Reality encourages the creation of innovative and fun learning experiences. 2) student engagement is significantly increased through active involvement of multiple senses and results in measurable improvement in learning outcomes. There are several challenges that need to be considered, namely: accessibility-related issues related to application design, the complexity of using AR systems, AR application development needs to go through iterative development cycles to accommodate diverse platform users, and the lack of pedagogical approaches when integrating AR applications into learning activities. The findings contribute to the discourse on technology integration in language education and offer practical insights for educators and policymakers who want to improve the overall effectiveness of Arabic language learning through innovative and brain-centred approaches. Abstrak Dalam lanskap pendidikan yang berkembang pesat, kemajuan teknologi baru-baru ini telah mengantarkan era baru kemungkinan metodologi pembelajaran inovatif. Penelitian ini berfokus pada integrasi prinsip Pembelajaran Berbasis Otak dengan teknologi Augmented Reality (AR) sebagai media pengajaran bahasa Arab. Penelitian ini termasuk penelitian kualitatif dengan jenis kepustakaan. Sumber data bersumber dari literature terkait Augmented Reality dan Pembelajaran Berbasis Otak. Metode analisis data menggunakan metode analisis isi. Hasil penelitian menunjukkan: 1) optimalisasi kinerja otak melalui integrasi Augmented Reality mendorong terciptanya pengalaman belajar yang inovatif dan menyenangkan. 2) keterlibatan siswa meningkat secara signifikan melalui keterlibatan aktif berbagai indera dan menghasilkan peningkatan yang terukur dalam hasil belajar. Ada beberapa tantangan yang perlu diperhatikan, yaitu: permasalahan terkait aksesibilitas berkaitan dengan perancangan aplikasi, kompleksitas penggunaan sistem AR, pengembangan aplikasi AR perlu melalui siklus pengembangan yang berulang untuk mengakomodasi pengguna platform yang beragam, dan kurangnya pendekatan pedagogi saat mengintegrasikan aplikasi AR ke dalam kegiatan pembelajaran. Temuan ini tidak hanya berkontribusi pada wacana tentang integrasi teknologi dalam pendidikan bahasa tetapi juga menawarkan wawasan praktis bagi para pendidik dan pembuat kebijakan yang ingin meningkatkan efektivitas pembelajaran bahasa Arab secara keseluruhan melalui pendekatan inovatif dan berpusat pada otak.